Identity, territories, and sustainability : challenges and opportunities for achieving the UN Sustainable Development Goals - Monaco, Salvatore (Emerald Publishing Limited, 2024)
Using the United Nations' 2030 Sustainable Development Goals as a reference framework, Identity, Territories, and Sustainability explores the interplay between territorial and collective identities, territorial policies, and their implications for environmental, economic, and social sustainability. Presenting a series of case studies from across the globe, Salvatore Monaco demonstrates how the meaning of sustainability can vary across different geographic contexts. Analysing specific policy initiatives, chapters stress the importance of considering the complex interweaving of social, cultural, political, historical, and biophysical factors in shaping different sustainability trajectories in each place. Providing tools for policy and practice, Monaco presents examples of how sustainable development can be achieved by recognizing the importance of involving local communities in the decision-making process, promoting social and environmental justice, and finding innovative solutions to complex problems. Addressing the urgent need to tackle the global challenges of poverty, inequality, and environmental degradation, this is highly valuable reading for those interested in implementing sustainable development strategies across a variety of contexts.